A protective and broadly binding antibody class engages the influenza virus hemagglutinin head at its stem interface - Holly C. Simmons; Joel Finney; Ryutaro Kotaki; Yu Adachi; Annie Park Moseman; Akiko Watanabe; Shengli Song; Lindsey R. Robinson-McCarthy; Valerie Le Sage; Masayuki Kuraoka; E. Ashley Moseman; Garnett Kelsoe; et al. (mBio)
ABSTRACT Influenza infection and vaccination impart strain-specific immunity that protects against neither seasonal antigenic variants nor the next pandemic. However, antibodies directed to conserved sites can confer broad protection. Here, we identify and characterize a class of human antibodies that engage a previously undescribed, conserved epitope on the influenza hemagglutinin (HA) protein. Prototype antibody S8V1-157 binds at the normally occluded interface between the HA head and stem. Antibodies to this HA head–stem interface epitope are non-neutralizing in vitro but protect against lethal influenza infection in mice. These antibodies bind to most influenza A subtypes and seasonal human variants, and are present at low frequencies in the memory B cell populations of multiple human donors. Vaccines designed to elicit these antibodies might contribute to “universal” influenza immunity.IMPORTANCEAntibodies to the influenza virus hemagglutinin (HA) protein confer the strongest protection against infection. Human antibodies elicited by infection and/or vaccination fail to protect against antigenically novel animal, pandemic, or human seasonal viruses. Improved vaccines are needed. We identify a novel class of antibodies that bind most divergent HA subtypes and all seasonal human HA antigenic variants tested. These antibodies confer protection from lethal influenza challenge in animal models. The corresponding epitope on the HA head is occluded by its interaction with the stem and is inaccessible in the well-resolved prefusion state. The immunogenicity of this head–stem interface indicates that poorly understood conformations of HA presenting widely conserved surfaces are explored in biochemical, cell-based, and in vivo assays. Head–stem interface antibodies warrant further investigation as an avenue to improve influenza vaccines and therapeutics.